2022
DOI: 10.21203/rs.3.rs-1598634/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cytokine Hub Classification of PASC, ME-CFS and other PASC-like Conditions

Abstract: Background Post-acute sequelae of COVID-19 (PASC) is a growing healthcare and economic concern affecting as many as 10%-30% of those infected with COVID-19. Though the symptoms have been well-documented, they significantly overlap with other common chronic inflammatory conditions which could confound treatment and therapeutic trials. Methods A total of 236 patients including 64 with post-acute sequelae of COVID-19 (PASC), 50 with myalgic encephalomyelitis-chronic fatigue syndrome (ME-CFS), 29 with post-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Cytokine profiling and clinical biomarkers can differentiate other infections and autoimmune diseases from TBIs. One study demonstrated that cytokine profiles of post-acute sequelae of COVID-19, post-treatment Lyme disease, and myalgic encephalomyelitis-chronic fatigue syndrome were distinct [ 68 ]. Future analysis into cytokines could determine how immune interactions affect the disease course of TBIs.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine profiling and clinical biomarkers can differentiate other infections and autoimmune diseases from TBIs. One study demonstrated that cytokine profiles of post-acute sequelae of COVID-19, post-treatment Lyme disease, and myalgic encephalomyelitis-chronic fatigue syndrome were distinct [ 68 ]. Future analysis into cytokines could determine how immune interactions affect the disease course of TBIs.…”
Section: Discussionmentioning
confidence: 99%